Functional Nasal Surgery in a Compromised Soft Tissue Envelope - Dunn, Brandyn S.; Madorsky, Simon (Facial Plastic Surgery, 2023)
Functional nasal surgery in the setting of a compromised soft tissue envelope (STE) requires significant planning and preparation. Proper preoperative evaluation is imperative to assess the degree of STE compromise and determine the best surgical approach. Alternative approaches to functional nasal surgery, such as limited access surgical approaches, should be considered to minimize complications while achieving functional improvement. Given the increased risk of ischemia and necrosis in individuals with a history of a compromised STE, a comprehensive postoperative treatment algorithm is necessary to identify and treat signs of early vascular compromise.
Keywords: nasal soft tissue envelope; compromised soft tissue envelope; functional nasal surgery; vascular compromise; necrosis